2015
DOI: 10.1007/s00702-014-1357-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of increased carotid intima–media thickness and lower plasma levels of vitamin C and vitamin E in old age subjects: implications for Alzheimer’s disease

Abstract: In light of the recent advances regarding the role of vascularity in Alzheimer's disease (AD) pathophysiology, the relationship between plasma levels and activities of the major antioxidant molecules and the carotid intima-media thickness (C-IMT) of older persons with no or very mild cognitive impairment was evaluated. The underlying hypothesis is that the IMT may be an indirect index of vascular damage in persons with low levels of plasma antioxidants. Plasma levels of vitamins A, C, E, of uric acid as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 48 publications
0
13
0
Order By: Relevance
“…Recent investigations suggested that low serum vitamin C levels, through inactivation of NO signaling, are independent risk factors of CVD and related to increased mortality [32]. More specifically, it has also been demonstrated that a decrease in vitamin C levels was associated with carotid endothelial damage in patients with atherosclerosis, highlighting the positive role of vitamin C and antioxidants on NO levels [33]. The co-occurrence of periodontitis in CAD patients may be a possible pathway for the observed deterioration of endothelial function via decreased vitamin C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Recent investigations suggested that low serum vitamin C levels, through inactivation of NO signaling, are independent risk factors of CVD and related to increased mortality [32]. More specifically, it has also been demonstrated that a decrease in vitamin C levels was associated with carotid endothelial damage in patients with atherosclerosis, highlighting the positive role of vitamin C and antioxidants on NO levels [33]. The co-occurrence of periodontitis in CAD patients may be a possible pathway for the observed deterioration of endothelial function via decreased vitamin C levels.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an adequate Vit C plasma level seems to be associated with less progression in carotid intima-media thickness (C-IMT)—the greater C-IMT is suggested to be a risk factor in predicting cognitive decline in the general population, in the elderly population and in patients with Alzheimer’s disease. Polidori et al showed significant decrease (with a linear slope) in Vit C level among old individuals with no or very mild cognitive impairment from the first to the fourth C-IMT quartile [ 82 ].…”
Section: Role Of Vitamin C In Neurodegenerative Diseasesmentioning
confidence: 99%
“…Milk protein allergy became a worldwide medical concern while most study paid attention to infants and young children but not old people. Old people in 71‐90 years old had higher morbidity of many diseases such as cancer and Alzheimer's disease, and their health conditions were usually not good . Allergic diseases could do harm to the old as badly as to children.…”
Section: Discussionmentioning
confidence: 99%
“…Old people in 71-90 years old had higher morbidity of many diseases such as cancer and Alzheimer's disease, and their health conditions were usually not good. 29,30 Allergic diseases could do harm to the old as badly as to children. Our result suggested that old people should be more careful about cow's milk.…”
Section: Discussionmentioning
confidence: 99%